Endothelin-1 levels in induced sputum samples from asthmatic and normal subjects. Issue 7 (July 1997) - Chalmers, G W; Thomson, L; Macleod, K J; Dagg, K D; McGinn, B J; McSharry, C; Patel, K R; Thomson, N C
Abstract : BACKGROUND: Endothelin-1 (ET-1) is a potent bronchoconstrictor which may have a role in the pathogenesis of asthma. The levels of ET-1 in saliva, induced sputum, and plasma from asthmatic and non-asthmatic subjects were compared. METHODS: Sputum induction was performed on 28 asthmatic subjects and nine normal volunteers. ET-1 levels were measured in plasma, saliva, and sputum samples and reversed phase high performance liquid chromatography (RP-HPLC) was performed on saliva and sputum samples. RESULTS: ET-1 was present in the following order of concentration in both normal and asthmatic subjects: saliva > sputum > plasma (saliva, median 30.1 and 23.9 pg/ ml, respectively; sputum, median 15.5 and 11.2 pg/ml; plasma, median 3.1 and 3.6 pg/ ml). There were no differences between asthmatic and normal subjects in the levels of ET-1 in each fluid. The levels of ET-1 in asthmatic subjects were not influenced by whether or not they were taking inhaled steroids. RP-HPLC of sputum and saliva confirmed the presence of ET-1 in these fluids. CONCLUSIONS: Levels of ET-1 can be measured in saliva and sputum obtained by sputum induction in asthmatic and healthy subjects and, although no difference was found in basal levels of ET-1 in sputum, saliva and plasma between normal subjects and asthmatics without bronchoconstriction, it is apparent that ET-1 is produced or released locally within the respiratory tract in concentrations higher than those in plasma.